The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ijerph17124365
|View full text |Cite
|
Sign up to set email alerts
|

Opening the Black Box: The Impacts of Environmental Regulations on Technological Innovation

Abstract: Environmental regulations (ERs) that can stimulate technological innovation (TI) are the key to enabling a win-win strategy that benefits both economic development and environmental protection. This study seeks to analyze the impacts of ERs on TI. Previous literature highlighted that the black box of TI can be decomposed into technology investment and technology transformation, but empirical studies on such a decomposition have largely been ignored. Moreover, a detailed discussion of the links between ERs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…Wang et al [21] conducted a study of six carbon trading pilot areas in China, and the results show that the impact of emissions trading on technological innovation is regionally different and may also produce different results due to different types of regulations or types of technological innovation. Li et al [22] found that environmental regulations have a non-linear effect on the efficiency of investment in technological innovation but not on their conversion efficiency.…”
Section: Literature Review and Theoretical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [21] conducted a study of six carbon trading pilot areas in China, and the results show that the impact of emissions trading on technological innovation is regionally different and may also produce different results due to different types of regulations or types of technological innovation. Li et al [22] found that environmental regulations have a non-linear effect on the efficiency of investment in technological innovation but not on their conversion efficiency.…”
Section: Literature Review and Theoretical Analysismentioning
confidence: 99%
“…According to the available literature, there is also abundant evidence that there are three main relationships between environmental regulation and export competitiveness. First, environmental regulations reduce export competitiveness [22,24,[26][27][28]. Second, environmental regulation improves export competitiveness [6,35,36].…”
Section: Hypothesis 1 Environmental Regulation (Er) Is Negatively Cor...mentioning
confidence: 99%
“…Clegg (1989) states that power is a capability premised on resource control. In an innovation network, an organization's technology-innovation capability is the most fundamental and important factor determining its influence (Li et al, 2020), and the most influential organization always has stronger capabilities for searching for and absorbing useful knowledge than others (Cohen and Levinthal, 1990;Prajogo et al, 2020).…”
Section: Formation Of Knowledge Power Originmentioning
confidence: 99%
“…At the same time, the profit-seeking nature of enterprises makes it less likely for them to take the initiative to achieve green technological innovation. Therefore, there is an urgent need for external imposed or directed intervention, i.e., environmental regulation [4].…”
Section: Introductionmentioning
confidence: 99%